Hambatan Komunikasi dalam Perkuliahan Daring pada Masa Pandemi Covid-19 - Abdul Malik (Universitas Serang Raya, 2021)
This study was conducted to obtain an overview of the communication barriers between lecturers and students during the online class in the Covid-19 pandemic. The method used in this research is a case study and descriptive qualitative in which the result obtained from the research and the processed of the data about the communication barriers that occur in online lectures are deeply processed. The collected data consists of primary data that is obtained from online interviews and discussions with informan. Secondary data is obtained from various literature sources related to information and policies online lectures. Based on the result of research, show that at least there are three communication barriers that take place in online lectures, namely technological, environmental, and psychological barriers. Those three barriers are considered as lecture processed disruptions which implicate that there are students' difficulties in studying and understanding the lecture material well.